The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jocn.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Time interval to surgery and outcomes following the surgical treatment of acute traumatic subdural hematoma

Abstract: Although the pre-surgical management of patients with acute traumatic subdural hematoma prioritizes rapid transport to the operating room, there is conflicting evidence regarding the importance of time interval from injury to surgery with regards to outcomes. We sought to determine the association of surgical timing with outcomes for subdural hematoma. A retrospective review was performed of 522 consecutive patients admitted to a single center from 2006–2012 who underwent emergent craniectomy for acute subdura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
1
26
1
1
Order By: Relevance
“…18 In particular, the delay to neurosurgery in previous studies has included various combinations of prehospital time, interfacility transfer time, and in-hospital time after reaching a place with neurosurgical capability. The time point used to calculate delays to neurosurgery has been variously defined as the injury occurrence time, 3,7,11,17,19,[21][22][23]25,29,30,32,33,[37][38][39][40][41][42][43][44][45] time of the call received by the emergency response system, 6 time of patients' ED arrival, 3,15,26,37,38 onset of the loss of consciousness, 13,28 and onset of traumatic decerebration. 12 Although all patients in the present study were treated with decompressive craniectomy, it remains controversial whether this procedure, when done specifically for elevated ICP, improves outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…18 In particular, the delay to neurosurgery in previous studies has included various combinations of prehospital time, interfacility transfer time, and in-hospital time after reaching a place with neurosurgical capability. The time point used to calculate delays to neurosurgery has been variously defined as the injury occurrence time, 3,7,11,17,19,[21][22][23]25,29,30,32,33,[37][38][39][40][41][42][43][44][45] time of the call received by the emergency response system, 6 time of patients' ED arrival, 3,15,26,37,38 onset of the loss of consciousness, 13,28 and onset of traumatic decerebration. 12 Although all patients in the present study were treated with decompressive craniectomy, it remains controversial whether this procedure, when done specifically for elevated ICP, improves outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon experience would also possibly affect the length of operative time. Similar to operative duration, a measure that has been broadly studied is the time it takes for patients to be taken to the operating room, classically known as injury-to-incision time [20] [21] found that subjects who underwent an early decompression with a mean injury-to-incision time of 4.5 hours had significantly favorable outcome than patients who underwent a delayed decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Another work found that longer injury-to-incision time is really associated with better outcome [20]. This, however, can be a selection bias of patients with more severe injuries needing to be operated on sooner.…”
Section: Discussionmentioning
confidence: 99%
“…Age was considered a significant prognostic factor in some studies. [ 6 7 14 15 ] Wilberger et al compared patients with ASDH older than 65 years of age and younger than 34 years old and concluded that mortality and functional recovery index were significantly different between the two groups. [ 6 ] However, in other studies, age did not have a significant effect on mortality.…”
Section: Discussionmentioning
confidence: 99%